Efficacy and safety analysis of transarterial chemoembolization combined with tyrosine kinase inhibitors and immune checkpoint inhibitors with or without microwave ablation for unresectable hepatocellular carcinoma: a retrospective, multicenter, case-control study - Wang, Nan; Xu, Jingwen; Zhan, Chengxu; Cao, Pikun; Xue, Tianyu; Li, Jinpeng; Wei, Zhigang; Ye, Xin (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the efficacy and safety of transarterial chemoembolization (TACE) combined with tyrosine kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) with or without microwave ablation (MWA) for unresectable hepatocellular carcinoma (uHCC).Materials and methodsThis retrospective study comprised 220 patients with uHCC who underwent TACE combined with a TKI and ICI with MWA (Group A: 105 patients (median age, 60 ± 10 years) and 82 (78.1%) were men) or without MWA (Group B: 115 patients (median age, 58.35 ± 10.27 years) and 97 (84.4%) were men) at multiple centers in China. The overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and safety were compared between the two groups.ResultsThe OS, PFS, and ORR in Group A were significantly higher than those in Group B (OS, 21.30 ± 8.25 vs. 15.49 ± 7.41 months, p < 0.0001; PFS, 14.29 ± 6.34 vs. 7.15 ± 4.53 months, p < 0.0001; ORR, 66.7% [70/105] vs. 31.3% [36/115], p < 0.0001). The multivariable Cox regression analysis revealed that the combination of MWA and a more favorable tumor response were significantly associated with improved OS (hazard ratio, 0.5261; 95% confidence interval, 0.3839–0.7182; p = 0.0005 and hazard ratio, 0.5770; 95% confidence interval, 0.4209–0.7886; p = 0.0016). Grade 3 or 4 adverse events occurred in 30/105 (28.6%) and 29/115 (25.2%) patients in Groups A and B, respectively.ConclusionThe combination therapy (TACE + TKIs and ICIs) with MWA showed higher safety and significantly better OS, PFS, and ORR for uHCC than that without MWA.